1993
DOI: 10.1159/000187207
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (6 Months) Cross-Over Comparison of Calcium Acetate with Calcium Carbonate as Phosphate Binder

Abstract: A previous short-term study of 10 weeks in 8 patients had shown us that with half the dose of elemental calcium, calcium acetate (CaAc) could control predialysis plasma phosphate (PPO4) as well as calcium carbonate (CaCO3) but that the incidence of hypercalcemia was not decreased. To better appreciate the value of CaAc in comparison to CaCO3, CaAc was given to 28 patients on chronic hemodialysis (6 men, 22 women, age 61 ± 14 years; dialyzate Ca: 1.5 mmol/l) for 6 months to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…Results of different calcium acetate studies in adults are not conclusive, demonstrating both a significant decrease [20] and increase [19,21,28] or even no change [24] in the incidence of hypercalcemia. Different medication with vitamin D metabolites may in part account for these differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results of different calcium acetate studies in adults are not conclusive, demonstrating both a significant decrease [20] and increase [19,21,28] or even no change [24] in the incidence of hypercalcemia. Different medication with vitamin D metabolites may in part account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in adult patients on chronic hemodialysis have shown calcium acetate to be superior to calcium carbonate in its ability to control hyperphosphatemia [12,[19][20][21][22][23][24][25][26][27][28]. The amount of orally ingested calcium taken as calcium acetate needed to bind phosphorus effectively is between 49% and 83% of that ingested with calcium carbonate [19,21,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hypercalcemia is more frequently observed with calcium carbonate than with calcium acetate [72,74]. Calcium acetate is poorly tolerated so that patient compliance may be worse than with calcium carbonate [73,75]. In patients on hemodialysis, concurrent use of a low-calcium dialysate (1.25 mmol/l) has significantly reduced the incidence of hypercalcemia with both of these calcium-based P i binders [76,77].…”
Section: Currently Available P I Bindersmentioning
confidence: 99%